2008
DOI: 10.1007/s11627-008-9143-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of auxin type and cytokinin concentration on callus induction and plant regeneration frequency from immature inflorescence segments of seashore paspalum (Paspalum vaginatum Swartz)

Abstract: Seashore paspalum (Paspalum vaginatum Swartz) is a salt tolerant, fine textured turfgrass used on golf courses in coastal, tropical, and subtropical regions. A callus induction and plant regeneration protocol for this commercially important turfgrass species has been developed. Induction of highly regenerable callus with approximately 400 shoots per cultured immature inflorescence (1 cm in length) was achieved by culturing 0.2 cm segments on media with 3 mg l −1 3,6-dichloro-2-methoxybenzoic acid (dicamba) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…A combination of 2, 4-D and BA was used in zoysia grass for the generation of callus with regeneration potential (Murugesan et al 2008). It was reported in seashore paspalum, that the use of dicamba significantly increased the plant regeneration frequency from immature inflorescence derived callus (Neibaur et al 2008). The use of dicamba was also identified as the most important factor in optimizing the tissue culture and stable genetic transformation response in barley (Castillo et al 1998;Trifonova et al 2001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A combination of 2, 4-D and BA was used in zoysia grass for the generation of callus with regeneration potential (Murugesan et al 2008). It was reported in seashore paspalum, that the use of dicamba significantly increased the plant regeneration frequency from immature inflorescence derived callus (Neibaur et al 2008). The use of dicamba was also identified as the most important factor in optimizing the tissue culture and stable genetic transformation response in barley (Castillo et al 1998;Trifonova et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Further, induction of embryogenic callus and subsequent of plant regeneration from young shoot meristems (Sairam et al 2002;Dalton et al 2003;Murugesan et al 2008) immature embryos (Christiansen et al 2005) and pistils (Gugsa et al 2006) has also been demonstrated. Immature inflorescences have been recognized as an important explants source for regeneration in many cereals and grasses (Neibaur et al 2008;Murugesan et al 2008;Yadav et al 2009). The present work is envisaged aiming at transferring salt tolerant trait from kallar grass to rice through somatic hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that BA in combination with auxins such as 2,4-D has a positive effect on callus induction in grasses (Altpeter and Posselt, 2000;Chaudhury and Qu, 2000;Bai and Qu, 2001). However, BA in combination with 2,4-D did not have a positive effect on callus induction in seashore paspalum turfgrass (Paspalum vaginatum Swartz) (Neibaur et al, 2008). The BA requirement may be species-specific (Chaudhury and Qu, 2000) and depends on the specific endogenous hormone levels (Bhaskaran and Smith, 1990).…”
Section: Effect Of Ba On Embryogenic Calli Inductionmentioning
confidence: 99%
“…Although vetiver callus induction usually prefers a high ratio of auxin to cytokinin, an optimal combination of auxin and cytokinin is still needed to be determined for each kind of explant. Supplementing auxin in CIM is essential for inducing division and development of callus cells into embryogenic cells, especially for monocotyledon plants (Mendoza and Kaeppler, 2002;Shah et al, 2003;Can et al, 2008;Neibaur et al, 2008). However, a high concentration of auxin in a medium may prevent cell differentiation (Gray, 1996).…”
Section: Effects Of Pgrs In Cim On Callus Induction and Plant Regenermentioning
confidence: 99%